The Three Months Balanced Diet Recommendation Education Could Improve Mother’s Knowledge and Compliance in Better Diet and Nutrient Intake for Stunted Children in Surabaya, Indonesia - Taufiqurrahman; Annas Buanasita; Luki Mundiastuti (Institute of Medico-legal Publications Pvt Ltd, 2021)
Intruduction: Stunting is a condition of low height for age in children that indicates a linear growth failure influenced to cognitive development for under two children. Balanced Diet Recommendation (BDR) specific for stunted children had not explore to get better outcome in nutrition. The purpose of this study was to analyze mother’s knowledge and compliance in giving better diet as well as energy, protein, Fe, zinc intake for stunted children after getting 3 months education on BDR. Methods: The study was pre-post-test one group quasy experimental study. A total of 150 stunted children were involved, selected from 36 primary health centers in Surabaya.The BDR was derived from Optifood Linear Programming and prepared it for stunted children in Surabaya. Education on BDR was provided 3 times within 3 months by trained supervised nutritionists. Mother’s compliance was assessed using the last 6 months Semi Quantitative Food Frequency and 2x24 hours food recall were used to measure nutrient intake. Height was measured with microtoise. The data were analyzed using paired t-test. Results: There was an improvement in mother’s knowledge and mothers’ compliance in giving better diet and nutrition intake to their stunted children. The mean of mother’s compliance increased from 8.3 to 10.4 (p=0.00) and nutrients intake of all respondents increased significantly (p=0.000). Prolonged education may have impact to height for age z- score.Conclusions: Education on locally specific BDR for stunting is an important approach to improve the dietary intake and nutrition status of stunted children.